Математическая модель структурной эволюции общественных производительных сил - Повещенко, Г.; Чеховой, Ю. (Социология: теория, методы, маркетинг, 2001)
Mathematical model of social productive forces structural evolution is discussed,
particularly with regard to evolution of social production of life. There are analyzed
some methodological grounds and issues of mathematical modeling, like correlation
between accuracy and complexity/simplicity of models. There are presented both
conceptual model of social production of life (by V.Khmelko) and mathematical model
developed according to the conceptual one.